Biosensing and biosensors: terminologies, technologies, theories and ethics - Misera, Jan; Melchert, Johannes; Bork-Hüffer, Tabea (Geography compass, 2024)
Which biosensing technologies are geographers using in their research, and what exactly do they measure? What are the theoretical origins of geographic interests in biosensing? This article provides an overview of the variety of biosensors applied in biosensing research, tracks the theoretical debates and roots of geographic engagement with biosensing, and discusses the potentials, limitations and ethical implications of applying biosensors. We critically reflect on the varied terminologies that have been used to describe a rapidly evolving array of biosensing technologies and methodologies and suggest a common understanding for key terms such as “biosensing” (technologies or methodologies), “biosensors,” “wearable biosensors” and “biosignals.” We offer an overview of the broader theoretical debates that have inspired geographers turn to biosensing, including behavioral geography, more-than-representational theory, critical neurogeography, the mobilities and biosociality paradigms, and visual geographies. These have called for methodologies that can capture affects neglected in representational research, follow people, things and technologies as they are mobile in space and time, investigate the links between brain, cognition and biopolitics or attend to visualities in everyday life. Although geographers have so far engaged with a limited number of the ever-growing variety of available (bio-)sensors, the development and application of biosensing methodologies is vibrant, highly diverse and very promising for diverse geographical research questions and fields. Going forward, we particularly encourage experimentation with eye-trackers, which come closest to measuring instantaneous responses to environmental stimuli and offer interesting opportunities for the analysis of social and material environments through the visual data they create. Finally, we conclude with a call for a stronger emphasis on data ethics, procedural ethics and ethics of care in biosensing, which have so far received too little attention in these often interdisciplinary and complex biosensing research endeavors.
Gesehen am 08.04.2025